LINE-1 Transcript Heterogeneity in Non-Small Cell Lung Cancers Is Driven by Host Genomic Context and Conserved Functional Hotspots. - Wang, Yingshan; Ramos, Kenneth S. (Cancers, 2026)
Simple Summary: Long interspersed element-1 sequences are normally silenced in healthy cells but frequently reactivated in cancer, where they contribute to genomic instability and transcriptional dysregulation. However, the determinants of their transcriptional heterogeneity in non-small cell lung cancer remain poorly defined. In this study, we systematically characterized locus-specific LINE-1 transcript expression across a large panel of non-small cell lung cancer cell lines to determine how genomic context shapes retrotransposon activity. We show that LINE-1 transcription is dominated by evolutionarily young elements and follows conserved chromosomal patterns across tumor subtypes, with the highest activity observed in lung squamous cell carcinoma. Importantly, LINE-1 expression is anchored by a small number of conserved genomic hotspot loci that remain active across tumor backgrounds and are located near cancer-relevant genes. These findings provide a genome-scale framework for understanding retrotransposon regulation in cancer and highlight conserved LINE-1 loci as potential markers of genome instability and regulatory vulnerability. Background: Long INterspersed Element-1 (LINE-1) retrotransposons comprise 17–20% of the human genome. These retroelements are normally silenced early in embryonic development through epigenetic mechanisms and reawakened during oncogenesis, leading to transcriptional dysregulation, genomic instability, and immune evasion. Methods: In the present study, we categorized LINE-1 transcripts across 121 non-small cell lung cancer (NSCLC) cell lines from the Cancer Cell Line Encyclopedia (CCLE) by subfamily, length, orientation, chromosomal origin, and distribution. In addition, high-prevalence insertions were mapped to nearby genes to assess potential functional interactions. Results: LINE-1 transcript abundance and length in NSCLC were dominated by evolutionarily young subfamilies, particularly L1HS and L1PA2 through L1PA5. Chromosomal patterns were conserved across NSCLC subtypes, with modest enrichment of L1HS activity on Chromosome 4 and the X Chromosome. The lung squamous cell carcinoma (LSQCC) subtype exhibited the highest total levels of L1HS expression relative to other NSCLC subtypes. Race modestly influenced LINE-1 transcript abundance, with cell lines derived from self-identified African American individuals showing elevated overall LINE-1 and L1HS expression. Age showed a weak positive correlation with total LINE-1 abundance. Integrative analysis revealed recurrent hotspots at 22q12.1 and 20p11.21 that were transcriptionally active across subtypes and coincided with previously reported intact LINE-1 elements active in epithelial cancers. Recurrent insertions were located near cancer-associated genes, including RB1, NEDD4, FTO, LAMA2, NOD1, and KCNB2, implicating LINE-1 activity in cis-regulatory remodeling of oncogenic pathways. Conclusions: Together, these findings indicate that LINE-1 transcript heterogeneity in NSCLC is shaped by host genomic architecture and conserved functional hotspots, providing new insights into the mechanisms of genetic and epigenetic dysregulation associated with LINE-1 retroelements.